Modelling and operation performance of the hybrid borehole heat exchangers constituted of a shallow U-pipe array and medium-deep coaxial pipe - Shilong Yang; Yaru Li; Lingfeng Huang; Qingbo Yang; Ke Zhu; Yudong Mao; Wenke Zhang; Mingzhi Yu (Energy and Buildings, 2026)

Ethylene-related gene regulation in rhododendrons under heat stress - Shida Xu; Fanyu Zeng; Xingmin Geng; Lingfeng Mao; Xiaoyue Lin (Horticulture, Environment, and Biotechnology, 2026)

Leaf Size Variation in Response to Climate Drivers Depends on Plant Life Form - Jiayi Lu; Shihao Wen; Siyu Chen; Yuran Dong; Xiuping Wu; Yao Li; Min Zhang; Zhiwei Ge; Jonathan M. Chase; Lingfeng Mao (Journal of Biogeography, 2026)
Aim Plant leaf size and shape vary across major climatic gradients, reflecting the mechanisms for how plants regulate the balance of carbon, water, and heat. However, the influence of climate on leaf traits can be confounded by multiple factors, and the complex variation among different plant groups remains insufficiently understood. Here, we investigated how climate influences leaf size traits and whether this effect is moderated by plant life form. Location China. Taxon Angiosperms. Methods Based on leaf length, width, and aspect ratio data from 26,726 angiosperm species distributed across major climate gradients in China, we analysed the effects of temperature and precipitation on leaf size traits, and compared differences among plant life forms (woody vs. herbaceous and evergreen vs. deciduous). Additionally, spatial heterogeneity was assessed across eight vegetation zones. Results Leaves are generally larger and rounder in warm and humid areas, and smaller and narrower in cooler and more arid areas. All leaf size traits respond more strongly to precipitation than temperature, with leaf length showing the strongest responses to both climate variables. Herbaceous and deciduous species exhibit stronger climate responses nationwide, whereas woody and evergreen species are more sensitive within vegetation zones. Key responsive traits show clear geographic shifts. Main Conclusions Overall, we find that leaf size and shape vary strongly across China, as a result of climate variation, but these patterns are modified by dominant regional ecological processes and the ecological strategies of plant life forms. These findings not only help clarify variation in plant traits along climatic gradients, but also provide a theoretical framework for predicting how different plant morphologies will respond to ongoing climate change.

Wheat density drives negative density dependence in nitrogen uptake and root plasticity in wheat–weed communities - Li Zhang; Weiqiang Liu; Yizhong Rong; Jiazhen Xi; Lingfeng Mao; Anna Gunina; Zhen Zhang (Rhizosphere, 2026)

Three ectomycorrhizal fungal inoculum modifies the growth performance and tolerance of Quercus nuttallii seedlings under salt stress - Nan Yang; Cheng Wan; Daoyuan Ren; Yan Zhang; Stefano Chelli; Zhengxue Zhu; Silvia Traversari; Giovanni Emiliani; Lingfeng Mao (Forest Ecology and Management, 2026)

Identifying divergence time and paleoclimate change hotspots for better conservation under future climate change - Yuheng Chen; Jonas J. Lembrechts; Yann Hautier; Dongfan Xu; Yao Li; Yuran Dong; Lingfeng Mao (Biological Conservation, 2025)

Positive contributions of China's protected areas in biodiversity conservation and carbon storage under future climate change - Xuede Dong; Jirui Gong; Frank Yonghong Li; Lingfeng Mao; Weiyuan Zhang; Siqi Zhang; Guisen Yang; Chenyi Yan; Ruijing Wang; Shangpeng Zhang; Tong Wang (Science of The Total Environment, 2025)

Safety and Probiotics Evaluation of Bifidobacterial Genomes Isolated from Probiotic Products - Jue Li; Yinhuan Wang; Xingyu Xu; Xiaoling Zheng; Zhengnan Wang; Xiaofeng Chen; Lei Wang; Lingfeng Mao; Wangqin Ge; Huijun Liu; Wenwen Gao; Tingzhang Wang; et al. (Current Microbiology, 2025)

Exploring the relationship between walls and urban biodiversity: a systematic review - Qinghua Xu; Ranxu Jia; Ranyang Zhang; Yuncai Wang; Lingfeng Mao; Hui Wang (Urban Ecosystems, 2025)

Diversification in birds is promoted by plant diversity, topographic heterogeneity and stable paleoclimate - Xinyu Wang; Lu Miao; Xiongwei Huang; Lingfeng Mao; Tianlong Cai; Jens‐Christian Svenning; Gang Feng (Journal of Biogeography, 2024)
Aims Long‐term climate stability, contemporary climate and environmental heterogeneity have been linked to bird diversity patterns through their direct impacts on diversification rate, as well as through their indirect effects on plant species richness, which could also directly and indirectly affect bird diversity. This study aimed to quantitatively assess whether these potential drivers could indirectly affect bird species richness through their direct effects on the diversification rate in birds in eastern Asia. Location Mainland China. Taxon Birds. Methods Using the distribution data of 1127 bird species across 320 prefecture cities in China and a phylogenetic tree of these bird species, we analysed the distribution patterns of bird species richness and diversification rate of all birds, passerine birds and non‐passerine birds, respectively. We also investigated their relationships with long‐term climate stability, contemporary climate, elevation range and plant diversity using ordinary least squares regression model and simultaneous autoregressive model. In addition, structural equation model was used to analyse whether these drivers could indirectly affect bird species richness through their direct effects on bird diversification rate. Results The results showed that bird species richness and diversification rate were highest in southwestern China. Additionally, diversification rate for passerine birds was higher than non‐passerine birds and all birds. Regression analyses revealed that plant species richness was the variable most associated with bird species richness and diversification rate across the three groups. Notably, results from structural equation model indicated that plant species richness, elevation range and glacial–interglacial climate change can indirectly influence bird species richness by directly affecting diversification rates. Main Conclusions These findings emphasize the importance of considering diversification rate when understanding the geographic distribution patterns of bird diversity. The direct and indirect effects of plant species richness, elevation range and glacial–interglacial climate change on bird diversity highlight the crucial role of mountain regions with higher plant diversity and stable paleoclimate in forming and maintaining biodiversity.

Doped microspheres for whispering gallery mode microlasing - Xiaoxuan Wang; Chaoyang Huang; Chuansheng Xia; Feifei Qin; Gangyi Zhu; Lingfeng Mao; Yi Ma; Zengliang Shi; Qiannan Cui; Chunxiang Xu (Science Bulletin, 2024)

Preparation of bacterial fertilizer from biogas residue after anaerobic co-digestion of kitchen waste and residual sludge - Chuan Li; Chang Hua; Lingling Chen; Zimei Miao; Rui Xu; Sili Peng; Zhiwei Ge; Lingfeng Mao (Environmental Science and Pollution Research, 2024)

Rain gardens enhance the taxonomic richness but not the abundance of soil invertebrates in urban ecosystems - Jingjing Wang; Lihao Guo; Saige Xu; Yan Zhu; Lingfeng Mao (Ecological Engineering, 2024)

Development of novel single fuel cell based on composite polar plates for highly efficient power generation - Caiying Zhou; Yancheng Wang; Deqing Mei; Wenze Mao; Lingfeng Xuan (Fuel, 2024)

Differentiation of fungal trophic guilds to long-term nitrogen addition in a poplar plantation - Nan Yang; Jiangbao Zhang; Jiani Hua; Baohan Song; Tianyi Wang; Wei Xing; Guobing Wang; Lingfeng Mao; Honghua Ruan (Forest Ecology and Management, 2024)

More than just pandas: Urgent research needed on China's native plant biodiversity - Yu-heng Chen; Yao Li; Yu-ran Dong; Min Zhang; Yong Yang; Richard B. Primack; Kathryn E. Barry; Lingfeng Mao (Biological Conservation, 2024)

Interaction among soil nutrients, plant diversity and hypogeal fungal trophic guild modifies root-associated fungal diversity in coniferous forests of Chinese Southern Himalayas - Nan Yang; Yan Zhang; Jingji Li; Xiuxiu Li; Honghua Ruan; Parag Bhople; Katharina Keiblinger; Lingfeng Mao; Dong Liu (Plant and Soil, 2022)

The relationship between green roofs and urban biodiversity: a systematic review - Linwen Wang; Hui Wang; Yuncai Wang; Yue Che; Zhiwei Ge; Lingfeng Mao (Biodiversity and Conservation, 2022)

Niche overlap and divergence times support niche conservatism in eastern Asia–eastern North America disjunct plants - Xue Yin; Scott Jarvie; Wen‐Yong Guo; Tao Deng; Lingfeng Mao; Minhua Zhang; Chengjin Chu; Hong Qian; Jens‐Christian Svenning; Fangliang He (Global Ecology and Biogeography, 2021)
Aim The plant species sharing ancestors now disjunctly distributed in eastern Asia (EAS) and eastern North America (ENA) have long been a biogeographic puzzle. Species within the EAS–ENA disjunct genera are presumed to exhibit niche conservatism, the tendency of closely related species to be more ecologically similar, reflecting lineages’ common evolutionary history. However, the hypothesis has not been well examined at the species level. Location EAS and ENA. Time period Current. Major taxa studied Species within the EAS–ENA disjunct genera. Methods We compiled data on climate, species occurrence, growth form, and phylogeny to examine niche conservatism. We first built a phylogenetic tree to select intercontinental congeneric pairwise species and obtained their divergence times. We then quantified the observed niche overlaps with Schoener’s D , which has a 0–1 range, based on species occurrence and climate of species’ native ranges. To obtain projected distributions, each species’ niche was projected to the non‐native region using ensemble ecological niche models. Projected‐related niche overlaps were then calculated using projected distributions and the corresponding climatic conditions. Results Average observed niche overlaps of congeneric pairwise species were relatively small: .124, .211 and .109 for all, herbaceous and woody species, respectively. Both observed and projected‐related niche overlaps had significant negative relationships with divergence times of intercontinental congeneric pairwise species, with niche overlap for herbaceous species being higher than that for woody plants when controlling for divergence times. Main conclusions We conclude that the significant negative relationships between niche overlap and divergence times of congeneric pairwise species confirm niche conservatism among species of EAS–ENA disjunct plants and that the extent of niche conservatism is slightly different for herbaceous and woody plants. These findings suggest the potential role of allopatric speciation in EAS, and could help to understand the evolutionary history and the Asian‐bias diversity pattern of the EAS–ENA disjunct plants.

Effects of climate and topography on the diversity anomaly of plants disjunctly distributed in eastern Asia and eastern North America - Xue Yin; Hong Qian; Xinghua Sui; Minhua Zhang; Lingfeng Mao; Jens‐Christian Svenning; Robert E. Ricklefs; Fangliang He (Global Ecology and Biogeography, 2021)
Aim Differences in physiography have been proposed to explain the diversity anomaly for vascular plants between environmentally similar regions of eastern Asia (EAS) and eastern North America (ENA). Here, we use plant species within disjunct genera to examine whether differences in topography contribute to the diversity anomaly and whether the richness–environment relationships differ between regions. Disjunct plants are used to ensure that the diversity anomaly relates to post‐disjunction evolution and diversification rather than regional differences in clade ages or immigration. Location EAS and ENA. Time period Current. Major taxa studied Plant taxa disjunctly distributed in EAS and ENA. Methods We compiled county‐level plant distribution data, and calculated species richness and variables of topography and climate within unit grid cells. We compared estimated coefficients of region effects among models, where richness was fitted with or without topography and climate. Topography and climate were also used to separately model within‐region spatial diversity patterns using spatial simultaneous autoregressive error models. Results The coefficients of region effects varied from −.776 for the model only including region to −.309 when topography was controlled for, but remained significant. Climate dominated the spatial diversity patterns in ENA. In contrast, the influence of climate (14.2%) on species richness was weaker than that of topography (18.3%) in the warm area of EAS. Relations to elevation and temperature varied between regions, shifting between positive and negative relationships in several cases. Main conclusions Our results demonstrate that variability in local topography contributes to the strong regional anomaly in plant species richness between EAS and ENA. Nevertheless, the diversity anomaly persists after controlling for local topography and climate. EAS and ENA also exhibit contrasting richness–environment relationships, providing another divergent aspect between the EAS–ENA disjunct floras. Our findings highlight that regional differences in topography or other environmental factors may underlie the diversity anomaly.

Regional disparity in extinction risk: Comparison of disjunct plant genera between eastern Asia and eastern North America - Houjuan Song; Alejandro Ordonez; Jens‐Christian Svenning; Hong Qian; Xue Yin; Lingfeng Mao; Tao Deng; Jian Zhang (Global Change Biology, 2021)
Climate and land cover changes are increasing threats to biodiversity globally. However, potentially varying biotic sensitivity is a major source of uncertainty for translating environmental changes to extinction risks. To reduce this uncertainty, we assessed how extinction risks will be affected by future human‐driven environmental changes, focusing on 554 species from 52 disjunct plant genera between eastern Asia (EAS) and eastern North America (ENA) to control for differences in environmental sensitivity at the genus level. Species distribution models were used to estimate and compare the vulnerability of species in disjunct genera between the two regions under two climate and land cover change scenarios (RCP2.6 and RCP8.5) in the 2070s, allowing to assess the effects of differences in climate and land cover pressures. Compared with ENA, stronger pressures from climate and land cover changes along with smaller range sizes in EAS translate into a larger number and proportion of species in disjunct genera becoming threatened by the 2070s. These regional differences are more pronounced under a best‐case climate scenario (RCP2.6), illustrating that strong climate change (RCP8.5) may override any regional buffer capacities. The main variables determining extinction risks differed between the two continental regions, with annual temperature range and cropland expansion being important in EAS, and annual precipitation being important in ENA. These results suggest that disparities in regional exposure to anthropogenic environmental changes may cause congeneric species with relatively similar sensitivity to have different future risks of extinction. Moreover, the findings highlight the context‐specific nature of anthropogenic effects on biodiversity and the importance of making region‐specific policies for conservation and restoration in response to the intensifying global changes.

Macro‐scale variation and environmental predictors of flowering and fruiting phenology in the Chinese angiosperm flora - Yanjun Du; Lingfeng Mao; Simon A. Queenborough; Richard Primack; Liza S. Comita; Arndt Hampe; Keping Ma (Journal of Biogeography, 2020)
Aim The timing of reproduction is a major determinant of the geographical distribution of plant species and resulting patterns of community assembly, yet few studies have assessed how the reproductive phenology of plant assemblages varies across large geographical and environmental gradients. In addition, it remains poorly known to what extent phenological trends and their drivers differ between flowering and fruiting phases or among different growth forms. To address these knowledge gaps, we examined the reproductive phenology and potential climatic drivers in herbaceous and woody species in ecosystems across China that varied in climate (temperate to tropical) seasonality and elevation. Location China. Methods We used data from the Flora Republicae Popularis Sinicae to estimate angiosperm flowering ( n = 16,717 species) and fruiting ( n = 11,605) phenology for 100 x 100 km grid cells ( n = 943) throughout China. We assessed large‐scale geographical trends in mean flowering and fruiting date and the time needed for fruit development. The relationships of these phenological variables with seven climate variables were examined using both ordinary and spatial linear regression. Results Higher latitudes and elevations had considerably reduced length of the reproductive season, with later flowering and earlier fruiting than lower latitudes and elevations. Woody plant assemblages flowered markedly earlier and needed three times longer for fruit development, and tended to show steeper geographical trends in reproductive phenology than herbaceous assemblages. Herbs and woody species differed strongly in their climatic triggers of flowering but largely shared the same cues for fruiting. Main conclusions Woody species compensate for longer seed development times by an earlier onset of flowering, yet reproduction in both life‐forms has stronger climatic constraints. Distinct climatic drivers suggest that herbaceous and woody species assemblages will respond differently to climate change. Overall, our findings underpin the role of reproductive phenology as a key biological mechanism through which climate shapes large‐scale geographical trends in species richness, phylogenetic diversity and community assembly.

High plant species richness and stable climate lead to richer but phylogenetically and functionally clustered avifaunas - Na Wang; Lingfeng Mao; Xueting Yang; Xingfeng Si; Yanping Wang; Wolf L. Eiserhardt; Gang Feng (Journal of Biogeography, 2020)
Aims Glacial–interglacial climate stability and contemporary climate could affect bird diversity through their direct effects on diversification and physiological tolerance, and indirect effects on plant species richness, which could provide more food and ecological niches. This study aims to quantitatively assess the direct and indirect effects of these drivers on species richness, phylogenetic and functional structure of bird assemblages. Location Mainland China. Taxon Birds. Methods Ordinary least squares models and simultaneous autoregressive models were used to test the associations between glacial–interglacial climate anomaly, contemporary climate, plant species richness, elevation range and species richness, phylogenetic structure, functional structure of bird assemblages in mainland China. Structural equation models were used to distinguish between direct and indirect effects of these variables on bird diversity. Results High bird species richness with phylogenetically and functionally clustered structure occurred in regions with more plant species and stable glacial–interglacial climate. Notably, the phylogenetically clustered bird assemblages were composed of young lineages. Contemporary precipitation and elevation range affected bird diversity through their indirect effects on plant species richness. Main Conclusions These findings suggest that more plant species and stable glacial–interglacial climate may promote bird diversity through their effects on in situ diversification and species dispersal rate in southwestern China. Therefore, the well‐preserved plant and bird diversity through the long‐term climate fluctuations should be of great importance of biodiversity conservation in China.

The geographic and climatic distribution of plant height diversity for 19,000 angiosperms in China - Lingfeng Mao; Nathan G. Swenson; Xinghua Sui; Jinlong Zhang; Shengbin Chen; Jingji Li; Peihao Peng; Guangsheng Zhou; Xinshi Zhang (Biodiversity and Conservation, 2020)

Species richness is a surrogate for rare plant occurrence, but not conservation value, in boreal plant communities - Varina E. Crisfield; Jacqueline M. Dennett; Catherine K. Denny; Lingfeng Mao; Scott E. Nielsen (Biodiversity and Conservation, 2020)

Species and phylogenetic endemism in angiosperm trees across the Northern Hemisphere are jointly shaped by modern climate and glacial–interglacial climate change - Gang Feng; Ziyu Ma; Brody Sandel; Lingfeng Mao; Signe Normand; Alejandro Ordonez; Jens‐Christian Svenning (Global Ecology and Biogeography, 2019)
Aims Phylogenetic endemism describes the extent to which unique phylogenetic lineages are constrained to restricted geographic areas. Previous studies indicate that species endemism is related to both past and modern climate, but studies of phylogenetic endemism are relatively rare and mainly focused on smaller regions. Here, we provide the first assessment of the patterns of species and phylogenetic endemism in angiosperm trees across the Northern Hemisphere as well as the relative importance of modern climate and glacial–interglacial climate change as drivers of these patterns. Location Northern Hemisphere. Major taxa Angiosperm trees. Methods Using tree assemblages at the scale of 100 km × 100 km grid cells and simultaneous autoregressive (SAR) models, we assessed the relationships between species endemism, phylogenetic endemism and modern climate variables, Last Glacial Maximum (LGM) to present temperature velocity. Results Species and phylogenetic endemism were associated with both modern climate and glacial–interglacial climate change, with higher values in areas with stable historical climate and warmer and wetter modern conditions. Notably, the multivariate SAR analyses showed that the combinations of variables with highest Akaike’s information criterion (AIC) weight always included both LGM–present climate instability and modern climate, that is, modern precipitation and temperature. Main conclusions Our results show that high phylogenetic endemism is partially dependent on long‐term climate stability, highlighting the threat posed by future climate changes to the preservation of rare, phylogenetically distinct lineages of trees.

Phylogenetic age differences in tree assemblages across the Northern Hemisphere increase with long‐term climate stability in unstable regions - Gang Feng; Ziyu Ma; Blas M. Benito; Signe Normand; Alejandro Ordonez; Yi Jin; Lingfeng Mao; Jens‐Christian Svenning (Global Ecology and Biogeography, 2017)
Aims Long‐term climate stability is hypothesized to drive the emergence of species assemblages with large species age differences due to the accumulation of relict species and relatively newly arisen species via reduced extinction and increased speciation. Few studies have addressed these predictions and so far no study has done so for plants across the Northern Hemisphere. Here, we linked Quaternary‐scale climate variability to phylogenetic age differences between the oldest and youngest group of species in tree assemblages in 100 km × 100 km grid cells across the Northern Hemisphere to test these predictions. Location Northern Hemisphere. Methods Last Glacial Maximum (LGM)‐to‐present shifts in temperature and precipitation were used as proxies for Quaternary‐scale glacial–interglacial climate variability. Simultaneous autoregressive (SAR) models were used to assess the relationships between phylogenetic age differences and Quaternary‐scale climate variability. Results We found that phylogenetic age differences overall were largest in China and smallest in Europe, and they declined with increasing temperature instability as predicted, but only in Europe and North America. In China, the relatively mild Quaternary climate changes did not appear to have strongly affected phylogenetic age differences in tree assemblages. Main conclusions Our results show that phylogenetically diverse assemblages with large phylogenetic age differences among species are associated with relatively high long‐term climate stability, with intra‐regional links between long‐term climate variability and phylogenetic composition especially strong in the more unstable regions. These findings point to future climate change as a key risk to the preservation of the phylogenetically diverse assemblages in regions characterized by relatively high paleoclimate stability, with China as a key example.

Phylogeny and the prediction of tree functional diversity across novel continental settings - Nathan G. Swenson; Michael D. Weiser; Lingfeng Mao; Miguel B. Araújo; José Alexandre F. Diniz‐Filho; Johannes Kollmann; David Nogués‐Bravo; Signe Normand; Miguel A. Rodríguez; Raúl García‐Valdés; Fernando Valladares; Miguel A. Zavala; et al. (Global Ecology and Biogeography, 2017)
Aim Mapping the distribution and diversity of plant functional traits is critical for projecting future changes to vegetation under global change. Maps of plant functional traits, however, are scarce due very sparse global trait data matrices. A potential solution to this data limitation is to utilize the known levels of phylogenetic signal in trait data to predict missing values. Here we aim to test existing phylogenetic comparative methods for imputing missing trait data for the purpose of producing continental‐scale maps of plant functional traits. Location North America and Europe. Methods Phylogenetic imputation models and trait data from one continent were used to predict the trait values for tree species on the other continent and to produce trait maps. Predicted maps of trait means, variances and functional diversity were compared with known maps to quantify the degree to which predicted trait values could estimate spatial patterns of trait distributions and diversity. Results We show that the phylogenetic signal in plant functional trait data can be used to provide robust predictions of the geographical distribution of tree functional diversity. However, predictions for traits with little phylogenetic signal, such as maximum height, are error prone. Lastly, trait imputation methods based on phylogenetic generalized least squares tended to outperform those based on phylogenetic eigenvectors. Main conclusions It is possible to predict patterns of functional diversity across continental settings with novel species assemblages for most of the traits studied for which we have no direct trait information, thereby offering an effective method for overcoming a key data limitation in global change biology, macroecology and ecosystem modelling.

High plant endemism in China is partially linked to reduced glacial‐interglacial climate change - Gang Feng; Lingfeng Mao; Brody Sandel; Nathan G. Swenson; Jens‐Christian Svenning (Journal of Biogeography, 2016)
Aim Endemic species are hypothesized to particularly occur in areas with relatively stable climates during the Quaternary glacial‐interglacial oscillations (orbitally forced species' range dynamics hypothesis). This hypothesis has received support in global studies and studies from regions highly affected by glaciations. Here, we test its applicability to Chinese endemic species, thereby testing it in a region that was relatively mildly affected by glaciations. Location China. Methods We tested for associations between endemic species richness and Quaternary climate change, current climate and topography. Changes in mean annual temperature ( MAT ) and annual precipitation ( MAP ) between the Last Glacial Maximum and present were used to describe Quaternary climate change. We used simultaneous autoregressive ( SAR ) models to account for spatial autocorrelation in predictors, and Random Forest modelling to deal with non‐linear relationships and better handle multicollinearity among predictor variables. To get a deeper understanding of the mechanisms involved we also performed analyses based on growth‐form (woody versus herbaceous plants) and species age (palaeo‐ and neoendemics). Results Single‐predictor SAR models showed that glacial‐interglacial MAT velocity always has higher explanatory power than current climate (with a pseudo r 2 difference of 0.581–0.604 between the best palaeoclimate and current climate predictors for models for all endemic plants). Model selection on multivariate SAR models (based on Akaike weights) and Random Forest modelling (based on correlations between predicted and observed species richness) always included at least one variable representing Quaternary climate change as well as one or more current climate variables. Quaternary climate‐change variables were generally of similar strength to the current climate predictors. Notably, the summed Akaike weight across all models in the relevant model set was always 1 for glacial‐interglacial MAT velocity. There were no clear differences with respect to growth forms or species age in the estimated importance of Quaternary climate change. Main conclusions The consistent association between long‐term climatic stability and high plant endemism in China provides strong evidence for the importance of Quaternary glacial‐interglacial climate changes in shaping the distribution of endemic species, even in regions relatively mildly affected by glaciations. Hence, even moderate climate changes may have strong, long‐term effects on species diversity patterns.

Phylogenetic constraints and trait correlates of flowering phenology in the angiosperm flora of C hina - Yanjun Du; Lingfeng Mao; Simon A. Queenborough; Robert P. Freckleton; Bin Chen; Keping Ma (Global Ecology and Biogeography, 2015)
Aim The phylogenetic constraint hypothesis of flowering phenology states that closely related species flower at similar times of the year. We test this hypothesis for the C hinese angiosperm flora and assess additional effects of growth form, deciduousness, pollination mode and fruit type. We further examine whether the phylogenetic conservatism of flowering phenology tends to increase from tropical to temperate latitudes. Location C hina. Methods The midpoint of flowering time for 19,631 angiosperm species present in C hina was compiled. The phylogenetic signal for flowering time was evaluated for the whole country using the B lomberg K ‐value (adjusted for circular data). We then regressed the phylogenetic signal for 28 provinces as a function of their latitude. An analysis of variance for circular data was conducted to test the differences among growth forms. W atson– W illiams tests for circular flowering data were used to compare flowering dates between deciduous and evergreen species, animal‐pollinated and wind‐pollinated species, and fleshy and non‐fleshy fruits. Results The results support the phylogenetic constraint hypothesis. The phylogenetic signal at the whole country scale was lower than that at the province scale. Phylogenetic signal was also lower at tropical latitudes than at temperate latitudes. Flowering dates were associated with biological traits, with growth form having the largest effect. Main conclusions Flowering phenology was constrained by phylogeny, and so one should account for phylogeny when studying the underlying drivers of phenology. The strength of phylogenetic conservatism appears weaker at larger scales and becomes stronger towards temperate regions. Flowering phenology also varies predictably according to biological traits such as growth form, suggesting that both phylogeny and traits could be used to inform the flowering times of species for which no phenology data are available. It remains to be tested whether the phylogenetic signal for other functional traits putatively related with flowering time also increases with latitude.

Spatial patterns and environmental correlates of bryophyte richness: sampling effort matters - Shengbin Chen; J. W. Ferry Slik; Lingfeng Mao; Jian Zhang; Rula Sa; Kexin Zhou; Jixi Gao (Biodiversity and Conservation, 2015)

Environmental determinants of geographic butterfly richness pattern in eastern China - Shengbin Chen; Lingfeng Mao; Jinlong Zhang; Kexin Zhou; Jixi Gao (Biodiversity and Conservation, 2014)

Genetic and morphological variation in the venus clam Cyclina sinensis along the coast of China - Yuming Zhao; Qi Li; Lingfeng Kong; Yuze Mao (Hydrobiologia, 2009)

Cloning and Characterization of a Novel Human Prefoldin and SPEC Domain Protein Gene (PFD6L) From the Fetal Brain - Jiayi Zhang; Lingfeng Liu; Xiaomeng Zhang; Feng Jin; Jinzhong Chen; Chaoneng Ji; Shaohua Gu; Yi Xie; Yumin Mao (Biochemical Genetics, 2006)

Molecular cloning and characterization of a novel human protein phosphatase 2C cDNA (PP2C ε) - Feng Jin; Chaoneng Ji; Lingfeng Liu; Jianfeng Dai; Shaohua Gu; Xianfei Sun; Yi Xie; Yumin Mao (Molecular Biology Reports, 2004)